ANALISA DAN PERANCANGAN SISTEM MOBILE CUSTOMS BERBASIS IOS PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Yuma Akbar; Dewa Gde Adi Murthi Udayana (CKI ON SPOT, 2021)
Information on tracking postal items and import duties on products or goods received by customsstakeholder is very necessary to be presented transparently. Therefore the Directorate General ofCustoms and Excise provides facilities for easy access to this information by using an iOS-basedmobile customs system. The method used in designing and developing iOS-based Mobile CustomsSystem is the waterfall method which in every process is corrected. Data source collection and fieldobservations were also conducted to understand business processes and problems that occurredbefore the implementation of the iOS-based Mobile Customs System. The results of the design anddeveloping of applications can run in accordance with the design that has been made by still payingattention to the applicable laws.